Stereoselective Synthesis of CF3‐Containing Spirooxindoles via 1, 3‐Dipolar Cycloaddition by Dipeptide‐Based Phosphonium Salt Catalysis. Issue 7 (21st February 2020) - Liu, Xin; Lu, Dongming; Wu, Jia‐Hong; Tan, Jian‐Ping; Jiang, Chunhui; Gao, Guowei; Wang, Tianli
Abstract: Reported here is an alternative method for asymmetric synthesis of the CF3 ‐substituted 3, 2′‐pyrrolidinyl spirooxindoles via 1, 3‐dipolar cycloaddition by employing dipeptide‐based chiral phosphonium salt as a phase‐transfer catalyst. Under the optimal reaction conditions, a variety of CF3 ‐substituted 3, 2′‐pyrrolidinyl spirooxindole derivatives were readily prepared in high yields as a single diastereomer with high enantiomeric access (>20:1  dr and up to 94% ee). Abstract :